Analyzing the Alignment of Fashion Graduates’ Knowledge Competencies with Industry Demands - Nurjanah, Fitri; Widihastuti, Widihastuti (Proceeding International Conference on Religion, Science and Education, 2026)
The ever-changing nature of the fashion industry demands that Diploma 4 in Fashion Technology graduates possess not only creative and technical skills but also a solid foundation of knowledge competences that comply with industry standards. The purpose of this study is to assess the alignment between students’ and graduates’ knowledge competences and the demands of the fashion industry. Utilizing a mixed-methods approach, quantitative data were gathered through questionnaires delivered to big and medium-sized industries in the Special Region of Yogyakarta, Indonesia. The subjects of the study included department heads, as well as students and graduates of Universitas Negeri Yogyakarta’s D4 Fashion Technology program. Qualitative data were collected through interviews, while data analysis techniques consisted of descriptive statistics and thematic coding. The data show that the level of connection between industry demands and graduates’ knowledge abilities is 82%, which is considered highly relevant. This implies that graduates have a solid theoretical understanding of design principles, garment construction, and material knowledge, as well as basic production and fashion technology principles, in-depth analysis of both custom-made and ready-to-wear garments, and fashion quality testing. Through interviews with students, an additional competency was added, namely understanding of creating using the Clo3 program. On the other hand, the industry determined that mastery of theoretical concepts in publicity analysis, promotion, and communication technology as a branding medium is deemed less important for fashion graduates. The level of relevance mentioned above shows that the current curriculum is in accordance with industry requirements. Nonetheless, ongoing renewal is necessary to ensure increased relevance for current industrial practices. The study underlines the significance of increasing collaboration between vocational program study and the fashion industry in order to connect intellectual capabilities with real-world standards. Such connection is critical for increasing graduate employability and ensuring the competitiveness of vocational fashion education.